Measles immunisation in children with allergy to egg. - Aickin, R. (BMJ Group, 1994)
OBJECTIVE--To examine the occurrence of adverse reactions to measles vaccine given as a single dose to children with egg allergy, and to determine if the administration of single dose to children with a positive result in an intradermal skin prick test with the vaccine is associated with adverse reactions. DESIGN--Review of results of immunisation and prospective study of 96 consecutively presenting children given intradermal skin testing with the vaccine. SETTING--Children's allergy centre. SUBJECTS--410 children sensitive to egg referred to the allergy unit for advice about measles immunisation. MAIN OUTCOME MEASURES--Nature and severity of reactions associated with the administration of measles vaccine. RESULTS--All children had a positive result in a skin prick test with egg white, and five had a positive result in a skin prick test with vaccine. Of 96 consecutive children, 46 had a positive result in an intradermal test with vaccine. After immunisation with a full dose (0.5 ml) of vaccine adverse reactions were associated with a mild reaction in four children, none of whom required treatment. Only one of the 46 children with a positive result in an intradermal vaccine skin test had a reaction associated with vaccine administration. None of the children with a positive result in a skin prick test with measles vaccine reacted to the vaccine. The rate of minor reactions to the vaccine not requiring treatment was 0.98% (95% confidence interval 0.27% to 2.48%) and serious reactions requiring treatment was 0% (0% to 0.9%). CONCLUSION--Children with IgE mediated allergic reactions to egg protein should be investigated and managed by practitioners with special knowledge in this subject. Measles immunisation should be performed in a setting where any adverse reactions can be dealt with appropriately. Skin tests and measles vaccine and desensitisation are not necessary.